THE RELIGIOUS-PSYCHOLOGICAL ASPECTS OF PATIENCE IN HADITHS (The Journal of Interdisciplinary Human Studies, 2026)
This article explores the concept of patience (sabr) in Islamic teachings,highlighting its religious, moral, and psychological dimensions. Patience is repeatedlyemphasized in the Qur’an and explained in detail in the Hadiths of the ProphetMuhammad صلى الله عليه وسلم, illustrating its importance for spiritual growth, emotional stability, andsocial harmony. From a religious-psychological perspective, patience is not only a moralvirtue but also a mechanism for managing stress, regulating emotions, and strengtheningresilience. By analyzing the Hadiths, this study demonstrates that patience contributesto inner stability, moral development, and the formation of adaptive coping strategies.
Keywords: patience; sabr; Hadith; religious; psychology; emotional stability; resilience